Designing and Application of Mathematical Model A Multi – Objectives for Assessment The Quality Of The Project : A Case Study at Saad Public Construction Company - مهدي نداء صالح; حسن نرمين فائق (Journal of Economics and Administrative Sciences, 2018)
Abstract This research aims to design a multi-objective mathematical model to assess the project quality based on three criteria: time, cost and performance. This model has been applied in one of the major projects formations of the Saad Public Company which enables to completion the project on time at an additional cost that would be within the estimated budget with a satisfactory level of the performance which match with consumer requirements. The problem of research is to ensure that the project is completed with the required quality Is subject to constraints, such as time, cost and performance, so this requires prioritizing multiple goals. The project of rehabilitating the sand filters unit was chosen as one of the projects of Saad General Company in Salah ad Din governorate to be the sample of the research, the case study method to reach the targets of the search, and used critical path method (cpm) and Microsoft project program because there are non-traditional relationships between the activities, as used Analytical Hierarchical Process (AHP) to estimate parameters of performance criteria, and finally, using the goal programming to assist the project management to achieve their multiple objectives simultaneously. The results of the research obtained from solving the mathematical model showed the importance of this method as well as its efficiency in achieving five goals that can be achieved simultaneously according to their priorities. These objectives include: completion of the project in the minimum time, extra cost become within the budget, and satisfactory performance level of 100% By minimizing design errors or errors that occur in the implementation site through continuous on-site supervision by the project manager, as well as listening and communicating with the customer, this helps improve the quality of the project.